An epidemiological study to assess the mental health status of pregnant women in a tertiary care hospital, Srinagar, Jammu and Kashmir, India - Rehman, Bilal ur; Ahmad, Javid; Kaul, Rauf ur Rashid; Haque, Mohammad Kaleem ul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy is a major psychological, as well as physiological event; women may find themselves unable to cope with additional demands of pregnancy. Mental illness during pregnancy-whether anxiety, depression or more severe psychiatric disorders-can have a significant negative impact on a mother and her baby. Poor psychological health has been associated with low birth weight, premature birth, perinatal and infant death, postnatal depression, as well as long term behavioural and psychological impacts on the child. Depressive disorders are a common source of disability among women. Mental health problems during pregnancy and postpartum periods are one of the alarming health issue among women. Community-based epidemiological data on antenatal depression from developing countries is scarce. This study was conducted to assess the mental health status of pregnant women attending antenatal clinic of tertiary care hospital, SKIMS, Srinagar (J and K). Methods: A cross sectional study was conducted over a period of six months from 1stSeptember 2016 to 28th February 2017 among randomly selected pregnant women attending antenatal clinic of tertiary care hospital, SKIMS, Srinagar. A total of 200 pregnant women formed the study subjects. Data was collected by interviewing the pregnant women using pre-designed, pre-tested, semi-structured questionnaire. Data was analysed using Statistical Programme for the social science (SPSS) version 19.0. Results: Amongst the study population, prevalence of depressive disorder was 26%. The depression was significantly increasing with advancing pregnancy and advancing age. Socio-economic status and depression was associated statistically significant (p=0.024). Women with bad relationship with in laws had significantly more depression compared to those who had good relationship with in laws (P=0.0037). The association between parity and depressive disorder was statistically insignificant(P=0,7144). Conclusions: When we care for mother we care for two live and live without psychological consideration is completely materialistic. A depressive symptom occurs commonly during 2nd and 3rd trimester of pregnancy, drawing attention to a need to screen for depression during antenatal care. Maternal health policies, a priority in developing countries, must integrate maternal depression as a disorder of public health importance. Intervention should target women in the early antenatal period.